The Anti-Acetylcholine Receptor Antibody Test in Suspected Ocular Myasthenia Gravis - Jung Jin Lee; Kyung Min Koh; Ungsoo Samuel Kim (Journal of Ophthalmology)
Aim. To estimate the clinical significance of anti-acetylcholine receptor antibody (anti-AChR-Ab) levels in suspected ocular myasthenia gravis. Methods. In total, 144 patients complaining of fluctuating diplopia and ptosis were evaluated for serum levels of anti-acetylcholine receptor antibody and their medical charts were retrospectively reviewed. Subjects were classified into three groups: variable diplopia only, ptosis only, and both variable diplopia and ptosis. We investigated serum anti-AChR-Ab titer levels and performed thyroid autoantibody tests. Results. Patients’ chief complaints were diplopia (N=103), ptosis (N=12), and their concurrence (N=29). Abnormal anti-AChR-Ab was observed in 21 of 144 patients (14.1%). Between the three groups, mean age, number of seropositive patients, and mean anti-AChR-Ab level were not significantly different (P=0.224, 0.073, and 0.062, resp.). Overall, 27.5% of patients had abnormal thyroid autoantibodies. Conclusion. The sensitivity of anti-AChR-Ab was 14.1% in suspected ocular myasthenia gravis and seropositivity in myasthenia gravis patients showed a high correlation with the presence of thyroid autoantibodies.